Reification of the Signified and Consumerization of Wedding Receptions “Sintê Mungêrjê” In The Gayo Lôt Society In Central Aceh District - Bakti, Indra Setia; Nirzalin; Abidin (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2020)
Gayo customs emphasizes the values ​​of mutual cooperation and religiosity. The ritual of